PERTUMBUHAN TEKI (Cyperus rotundus L) DAN HASIL BAWANG MERAH (Allium ascalonicum L) AKIBAT SAAT INFESTASI DAN KERAPATAN AWAL YANG BERBEDA - Triyono, Kharis - (Eksplorasi, 2003)
ABSTRACT People nutsedge is an important weed, because beside complete also excreted the allelopathy. Related in cultivated crop, decreased of growth and yield due to this important weed was studied. Weed growth performance due to different of material propogation on number and infestation pweiod ia very important to study either. Onion as a cultivatwd crop was planted on this ewsearch bwcause it has height nutrient value, Research was conducted on pots, in gren house Mojosongo at an altitude 125 m above sea level, ans started on April 2002 until August 2002. Completely Randomizes Block Design two factors was used on this research. The first factors was early density of weed (P) 2,4,6 tubers per pot. The second factors wasÂ investationperiod (1): 2 weeks before planting, timely planting, 2 weeks and 4 weeks after onion planting. Result of this research showed that different in infestation period caused different early density did not cause different in growth and yiel of onion but that different in infestation period caused different in growth and yield of onion. The highest result weight of bulbs was found on combination of treatment P3I4(density 6 tuber per pot and investation periode 4 weeks after planting) 96,03 gr Key word : Purple nutsedge, onion, density, infestation